Energy expenditure in myelofibrosis patients treated with a JAK1/2 inhibitor - Tremblay, Douglas; Dougherty, Mikaela; Mascarenhas, John; Gallagher, Emily Jane (Frontiers in Endocrinology, 2023)
Weight gain is a known adverse effect of ruxolitinib, a JAK1/2 inhibitor that is the mainstay of treatment for many patients with myelofibrosis. The mechanisms behind weight increase with ruxolitinib is incompletely understood, although decreased adipose tissue lipolysis and increased appetite due to blocking the effects of leptin in the hypothalamus have been proposed. In order to explore the metabolic changes in ruxolitinib-treated patients with myelofibrosis, we performed a pilot study to assess the feasibility of using a portable indirect calorimeter to quantify energy expenditure before and during ruxolitinib treatment and report the results of two patients. Waist circumference increased during ruxolitinib treatment in both patients. Energy expenditure initially increased followed by a decrease and then increase again, but to levels below baseline. These results suggest that weight gain secondary to ruxolitinib may be related to changes in whole body energy expenditure.